Artificial Intelligence Integration and Students’ Digital Literacy as Determinants of Learning Outcomes in an Economics Education Assessment Course - Supriyadi; Ayu Nurul Amalia (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2025)
Education in the era of the Industrial Revolution 4.0 and Society 5.0 has undergone a substantial paradigm shift alongside the growing adoption of disruptive technologies, particularly artificial intelligence (AI), within learning processes. This study examines the influence of AI technology implementation and students’ digital literacy on learning outcomes in the Economics Learning Evaluation course. A quantitative survey design was applied involving fifth-semester undergraduate students enrolled in the Economics Education program. From a population of 90 students, a sample of 79 respondents was selected using random sampling based on the Isaac and Michael table at a 1% significance level. Data were collected through valid and reliable instruments and analyzed using partial regression and multiple regression techniques. The findings indicate that AI technology implementation and digital literacy each have a positive and statistically significant effect on students’ learning outcomes in the Economics Learning Evaluation course. The results confirm that the integration of AI technology, accompanied by adequate digital literacy, constitutes an essential factor in improving learning outcomes in economics education at the higher education level.